Investigation of the Characteristics of CO (1-0) Line Integrated Emission Intensity in Extragalactic Spirals - A., Dua’a K.; Al Najm, M. N. (Iraqi Journal of Science, 2022)
This paper aims to deal with the understanding of the properties of the molecular gas hydrogen in the extragalactic spirals sample. It is critical to make observations of CO (J = 1-0) line emission for spiral galaxies, particularly those with an energetic nucleus. In the sample of spiral galaxies compiled, a carbon monoxide CO (1-0) emission line can be observed. This sample of galaxies' gas kinematics and star-forming should be analyzed statistically utilizing appropriate atomic gas HI, molecular gas H2, infrared (1μm-1000μm), visual (at λblue-optical=4400A0), and radio spectrum (at νradio=1.4 GHz and 5GHz) databases. STATISTICA is software that allows us to perform this statistical analysis. The presence of a high scale of star formation activity in these galaxies is dependent linearly on the correlations between galactic luminosities. Our findings show that thermal radio luminosity and LFIR are closely related to CO line luminosity. Further, LCO and MH2 have a steep linear relationship, where the slope of the regression log LCO - LogMH2 equals 1. The LCO-SFR and LFIR-SFR relationship slopes are nearly linear (slope ~1), with a strong partial correlation RCO-SFR of 0.73 between LCO-SFR and a significant correlation RFIR-SFR of 0.5 between LFIR-SFR, according to the statistical analysis. The correlation between the rate of star formation (SFR) and hydrogen gas in spirals is significant in several fields of astrophysics. Hence, it is asserted that the important point of the current study is that there is a significant link between SFR and the actual amount of cold hydrogen gas (Mgas) for the simple reason that in our spiral analysis, the mean atomic cold gas amount quantity is almost 6 times greater than the molecular gaseous amount.